Controversies over stakeholder participation in marine protected area (MPA) management: A case study of the Cabo de Palos-Islas Hormigas MPA. (15th July 2017) - Hogg, Katie; Noguera-Méndez, Pedro; Semitiel-García, María; Gray, Tim; Young, Sarah
Abstract: There is considerable controversy over the role of stakeholder participation (SP) in the management of marine protected areas (MPAs). On the one hand, SP advocates claim that successful MPAs make use of SP in their design and management. On the other hand, SP critics argue that it is difficult to reach consensus between stakeholders on the need for MPAs, let alone the best way to manage them. This study aimed to investigate the extent of SP in the Cabo de Palos-Islas Hormigas MPA (CPH-MPA) in the Murcia province of south-eastern Spain, with a view to exploring this controversy. The research focused on: the perceptions of respondents on the value of SP in CPH-MPA decision-making; the current extent of SP in the CPH-MPA; the challenges to it; and ways of overcoming those challenges. Fieldwork was carried out during 2013–2015 involving the collection of qualitative data from key informant interviews, community meetings, and individual surveys. These data revealed a high degree of support for SP; very different perceptions about its current extent in CPH-MPA; the existence of many barriers to SP; and several recommendations to address these barriers. The study concluded that since immediate consensus on SP was absent, an experimental approach of adaptive co-management (ACM) could be adopted to determine what kind of SP works best. Highlights: The paper is based on rich primary data. The MPA case studied is unusual in being established to benefit fishers. Results show differences in perception of the extent of, and obstacles to, stakeholder participation (SP) in CPH-MPA. Stakeholder support for CPH-MPA suggests that resolving problems such as user conflicts, should not be insuperable. The paper concludes that, as in many other cases, solutions depend on political will.